Carbohydrate‐Based Ferrocenyl Boronate Esters: Synthesis, Characterization, Crystal Structures, and Antibacterial Activity. Issue 30 (10th September 2013) - Rami Reddy, E.; Trivedi, Rajiv; Giribabu, L.; Sridhar, B.; Pranay kumar, K.; Srinivasa Rao, M.; Sarma, A. V. S.
Abstract: A set of ferrocenyl boronate esters based on carbohydrate scaffolds was designed and synthesized efficiently by the reaction of ferroceneboronic acid with protected sugar diols derived fromD ‐xylose, L ‐sorbose, andD ‐mannitol in good yield. These compounds identified as 1, 2‐ O ‐isopropylidene‐α‐D ‐xylofuranose‐3, 5‐ferrocenyl boronate (3a ), 1, 2‐ O ‐cyclohexylidene‐α‐D ‐xylofuranose‐3, 5‐ferrocenyl boronate (3b ), 1‐ O ‐benzyl‐2, 3‐ O ‐isopropylidene‐α‐L ‐sorbofuranose‐4, 6‐ferrocenyl boronate (3c ), 1, 2:5, 6‐di‐ O ‐isopropylidene‐D ‐mannitol‐3, 4‐ferrocenyl boronate (3d ), and 1, 2:5, 6‐di‐ O ‐cyclohexylidene‐D ‐mannitol‐3, 4‐ferrocenyl boronate (3e ), were isolated as air‐ and moisture‐stable orange/yellow crystalline solids. All of the six‐membered (3a, 3b, and3c ) and five‐membered (3d and3e ) cyclic boronate esters were fully characterized by IR, multinuclear NMR ( 1 H, 13 C and 11 B), and UV/Vis spectroscopy, and also elemental analysis. The electrochemical behavior of the synthesized ferrocenyl boronate esters containing carbohydrates was investigated. Furthermore, the structures of3a and3c were unambiguously established by single‐crystal X‐ray diffraction analysis. The compounds have been screened for in vitro antibacterial activity against various Gram‐positive and Gram‐negative bacteria. They exhibited moderate to good inhibitory activity against the tested bacterial strains in comparison with standard drugs. Abstract : Ferrocenyl boronate esters of carbohydrates are prepared and characterized by spectroscopic and electrochemical techniques. The antibacterial activity of these esters is investigated.